Cumulative Transcutaneous Spinal Stimulation with Locomotor Training Safely Improves Trunk Control in Children with Spinal Cord Injury: Pilot Study - Liubov Amirova; Anastasia Keller; Goutam Singh; Molly King; Parth Parikh; Nicole Stepp; Beatrice Ugiliweneza; Yury Gerasimenko; Andrea L. Behrman (Children, 2025)
Background/Objectives: Non-invasive spinal cord transcutaneous stimulation (scTS) has expanded the therapeutic landscape of spinal cord injury (SCI) rehabilitation, offering potential benefits beyond compensatory approaches to paralysis. Children with SCI are particularly susceptible to developing neuromuscular scoliosis due to trunk muscle paralysis and ongoing skeletal growth, making targeted interventions crucial. As demonstrated in adults and pediatrics with SCI, the ability of scTS to acutely and safely enable an upright posture and trunk control could be leveraged as a therapeutic adjunct. Activity-based locomotor training (AB-LT) alone significantly improves trunk control in children with SCIs; combining it with scTS may enhance outcomes. This pilot study evaluated the safety, feasibility, and cumulative effects of AB-LT combined with scTS on trunk control in children with SCI. Methods: Three children with SCI completed 19 to 64 sessions of combined AB-LT and scTS. Adverse effects were monitored session to session, and trunk control was assessed pre- and post-intervention. Results: Across 130 interventions in three participants, 88.5% of sessions were free from adverse effects. Reported adverse events included autonomic dysreflexia (5.4%), skin redness at electrode sites (4.6%), and headaches (1.5%). No significant impact of scTS on fatigue or central hemodynamic parameters was observed. Post-intervention, all participants demonstrated improved trunk control during quiet and perturbed sitting. Conclusions: These findings provide the first evidence supporting the safety and feasibility of this combinatorial approach in pediatric SCI rehabilitation while emphasizing the importance of monitoring skin integrity and signs of autonomic dysreflexia. This intervention shows potential synergistic benefits, warranting further research to confirm efficacy and optimize therapeutic protocols.